2023
DOI: 10.1371/journal.ppat.1011400
|View full text |Cite
|
Sign up to set email alerts
|

Functional characterization of the gonococcal polyphosphate pseudo-capsule

Abstract: Neisseria gonorrhoeae is an exclusively human pathogen able to evade the host immune system through multiple mechanisms. Gonococci accumulate a large portion of phosphate moieties as polyphosphate (polyP) on the exterior of the cell. Although its polyanionic nature has suggested that it may form a protective shield on the cell surface, its role remains controversial. Taking advantage of a recombinant His-tagged polyP-binding protein, the presence of a polyP pseudo-capsule in gonococcus was demonstrated. Intere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 63 publications
0
7
0
Order By: Relevance
“…We observed a significant increase in cellular, extracellular, and cell surface polyP in response to INH. Compared to log-phase cells, stationary phase Mtb have more polyP and are more resistant to killing by INH [27, 53], and capsular polyP accumulation protects N. gonorrhoeae from antibiotics [23, 24]. Combining these observations, one possibility is that Mtb increase polyP in response to INH as a protective measure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We observed a significant increase in cellular, extracellular, and cell surface polyP in response to INH. Compared to log-phase cells, stationary phase Mtb have more polyP and are more resistant to killing by INH [27, 53], and capsular polyP accumulation protects N. gonorrhoeae from antibiotics [23, 24]. Combining these observations, one possibility is that Mtb increase polyP in response to INH as a protective measure.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to intracellular polyP, bacteria also have extracellular polyP. The pathogenic bacterium Neisseria gonorrhoeae has polyP in its capsule, and the polyP potentiates resistance to antimicrobials [23, 24]. We observed that both Mtb and M. smegmatis accumulate extracellular polyP [27].…”
Section: Introductionmentioning
confidence: 99%
“…We observed a significant increase in cellular, extracellular, and cell surface polyP in response to INH. Compared to log-phase cells, stationary phase Mtb have more polyP and are more resistant to killing by INH (Herbert et al, 1996 ; Rijal et al, 2020 ), and capsular polyP accumulation protects N. gonorrhoeae from antibiotics (Mookherjee et al, 2013 ; Manca et al, 2023 ). Combining these observations, one possibility is that Mtb increase polyP in response to INH as a protective measure.…”
Section: Discussionmentioning
confidence: 99%
“…Pathogenic bacteria lacking PPK or having reduced PPK levels exhibit defects in stress response, quorum sensing, growth, survival, and virulence (Rao et al, 1998 ; Rashid and Kornberg, 2000 ; Rashid et al, 2000 ; Chavez et al, 2004 ; Sureka et al, 2009 ; Zhang et al, 2010 ; Mookherjee et al, 2013 ; Manca et al, 2023 ). For instance, intracellular polyP is necessary for the survival of Mtb in host cells (Chavez et al, 2004 ; Sureka et al, 2007 ; Chuang et al, 2013 ; Singh et al, 2013 ), and deletion of PPK1 in M. smegmatis attenuates the survival of ingested M. smegmatis in human macrophages (Rijal et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation